Interpersonal relationships : - Arnold, Elizabeth (Saunders, 2003)
This book provides fundamental information about communication theory and applications for the student nurse, a reference text for clinicians interested in developing specific aspects of the nurse-client relationship, and source data for continuing staff development and patient education